Hazardous drinkers in the accident and emergency department – who attends an appointment with the alcohol health worker?. Issue 10 (27th September 2005) - Patton, R; Crawford, M; Touquet, R
Abstract : Aims: To identify factors that predict attendance at a brief assessment and referral session among patients identified as hazardous drinkers while being treated in an accident and emergency department. Methods: Patients presenting to an accident and emergency department (AED) were screened using the Paddington Alcohol Test (PAT). All patients identified as hazardous drinkers were given written information and offered an appointment with an alcohol health worker (AHW) to discuss their drinking. Data was collected on patients' age, gender, presenting condition, and alcohol consumption. Binary logistic regression was used to identify variables that predicted attendance at the appointment with the AHW among those who accepted advice. Results: Patients who attended the appointment were older than those who did not. Those who believed their attendance in the AED was related to alcohol were also more likely to receive brief intervention. Conclusions: Clinicians should explore patients' perceptions of the link between their alcohol consumption and AED attendance, and where appropriate emphasise the potential association.